A Comparison of Burnout Frequency Among Oncology Physicians and Nurses Working on the Frontline and Usual Wards During the COVID-19 Epidemic in Wuhan, China - Wu, Yuan; Wang, Jun; Luo, Chenggang; Hu, Sheng; Lin, Xi; Anderson, Aimee E.; Bruera, Eduardo; Yang, Xiaoxin; Wei, Shaozhong; Qian, Yu (Journal of pain and symptom management, 2020)
The epidemic of coronavirus disease 2019 (COVID-19) was first identified in Wuhan, China and has now spread worldwide. In the affected countries, physicians and nurses are under heavy workload conditions and are at high risk of infection. The aim of this study was to compare the frequency of burnout between physicians and nurses on the frontline (FL) wards and those working in usual wards (UWs). A survey with a total of 49 questions was administered to 220 medical staff members from the COVID-19 FL and UWs, with a ratio of 1:1. General information, such as age, gender, marriage status, and the Maslach Burnout Inventory—medical personnel, were gathered and compared. The group working on the FLs had a lower frequency of burnout (13% vs. 39%; P < 0.0001) and were less worried about being infected compared with the UW group. Compared with medical staff working on their UWs for uninfected patients, medical staff working on the COVID-19 FL ward had a lower frequency of burnout. These results suggest that in the face of the COVID-19 crisis, both FL ward and UW staff should be considered when policies and procedures to support the well-being of health care workers are devised.